Establishment of a knowledge management system for the R&D Department of Company ABC's Flavor Division - Sinson, Cherrie Lou L. (University of the Philippines Diliman, 2013)
This project was conducted to establish a simple yet comprehensive Knowledge Management System (KMS) for the Flavor Division's R&D Department of Company ABC which is a flavor and fragrance company. Based on a KM Assessment conducted using a questionnaire and interviews, the following operational processes were identified as points of interest : R&D training, formulation management, and project tracking. Using KM concepts and strategies, tools were designed and implemented with the end goal of utilizing KM for the department's sustainable and competitive advantage. For R&D training, templates and databases were designed for the implementation of Standard Operating Procedures (SOP), Seminar and Training Reports (STR) and Lessons Learned Reports (LLR). For formulation management, a formulation repository was created that now serves as the heart of the R&D Department. For project tracking, a tool called Project Tracking and Feedback System (PTFS) was developed to track the whole division's project process as well as a means of communication between Company ABC and its principals. Regular Lessons Learned Sessions (LLS) are conducted to review the KMS and to evaluate the information rendered from the system as possible idea source for improvements and solutions to current processes. After several weeks of implementation of the KMS, the users were able to take advantage of the benefits of the new system with a more organized and efficient operational processes not only for the R&D Department, but the whole Flavor Division. This project recommends continuous build-up of the KMS to cover other business processes for the overall improvement of the organization.